Longitudinal Changes in Diet Quality over Adulthood and Physical Function in Older Life: Findings from a British Birth Cohort. (29th May 2020) - Tektonidis, Thanasis; Coe, Shelly; Esser, Patrick; Maddock, Jane; Buchanan, Sarah; Mavrommati, Foteini; Izadi, Hooshang; Schott, Jonathan M; Richards, Marcus; Dawes, Helen
Abstract: Objectives: A healthy diet has been linked to better physical function in older adults but evidence on the role of cumulative dietary exposure is scarce. Sex differences in the relationship are also underexplored. The objective was to explore the longitudinal association of diet quality in adulthood (from 36–64 y), in line with dietary guidelines, and walking speed as an objective measure of later life physical function. Methods: Study sample was derived from the Insight 46 ( n  = 502), a neuroscience sub-study of the longitudinal National Survey of Health and Development, UK. Diet was assessed four times, at age 36 y, 43 y, 53 y and 60–64 y using five-day food diaries, from which the Healthy Eating Index-2015 (HEI) was calculated (0 - low quality, 100 - high quality). Walking speed was estimated in a 10-meter walk test at self-selected pace, using an inertial measurement unit at age 69–71 y. Linear mixed models with random effects and group-based trajectory modeling were used to assess individual and group changes in HEI in adulthood. Multivariable linear regression models with sex as modifier, controlling for multiple characteristics assessed the association between adulthood HEI trajectories and walking speed at 71 y. The final sample was 226 women and 230 men. Results: Men and women improved diet quality linearly in adulthood (β: 0.6 HEI/y, 95% CI: 0.5, 0.7). Three linear HEI trajectories were identified (21% "Low" βo: 33, β: 3.6; 59% "Medium" βο: 38, β: 6.1; 20% "High" βο: 52, β: 5.5, P  < 0.001). Women had faster increase rates, higher HEI at each age (β: 4 HEI points, 95% CI: 3, 6) and were more likely to belong to the "High" HEI trajectory than men (β: 1.97, P  < 0.001). There was no overall association but in women a 10 point increase in predicted HEI trajectory and membership in the "High" vs "Medium"-"Low" HEI trajectories were associated with faster walking speed (β: 0.04 m/s, 95% CI: 0.01, 0.08, β: 0.06 m/s, 95% CI: 0.01, 0.11, respectively). Association was attenuated in multivariable models. No association was observed in men. Conclusions: In women, higher diet quality in adulthood was associated with faster walking speed in later life. Achieving and maintaining high diet quality in adulthood is likely of importance to yield benefits in physical function. Funding Sources: Medical Research Council UK Alzheimer's Research UK Dementias Platform UK Wolfson Foundation UK CLOSER UK.